1993
DOI: 10.1007/bf00685880
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depletion increases the cytotoxicity of melphalan to PC-3, an androgen-insensitive prostate cancer cell line

Abstract: Prostate cancer that is androgen-insensitive is unresponsive to a wide spectrum of cytotoxic agents, including all of the alkylating agents. Since a major pathway for the detoxification of the alkylating agents is conjugation with glutathione (GSH), GSH depletion has proved to be effective as a technique to restore melphalan sensitivity in melphalan-resistant cancer cell lines. However, the effect of GSH depletion has not been widely studied in tumor cell lines that have not developed resistance due to previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Cisplatin also behaves like an alkylating agent, and therefore a similar modulation mechanism might be involved. Both GSH depletion by BSO and GST inhibition have increased the tumoricidal activity of melphalan, a proteolytic alkylating drug (38), supporting the present view of involvement of cisplatin-mediated decrease of GSH and inhibition of GST in its anticancer activity. This is further strengthened by the results of the experiments involving combined treatment with BSO, a GSH depleting agent, with cisplatin.…”
Section: Discussionsupporting
confidence: 84%
“…Cisplatin also behaves like an alkylating agent, and therefore a similar modulation mechanism might be involved. Both GSH depletion by BSO and GST inhibition have increased the tumoricidal activity of melphalan, a proteolytic alkylating drug (38), supporting the present view of involvement of cisplatin-mediated decrease of GSH and inhibition of GST in its anticancer activity. This is further strengthened by the results of the experiments involving combined treatment with BSO, a GSH depleting agent, with cisplatin.…”
Section: Discussionsupporting
confidence: 84%
“…GSH depletion through buthionine sulfoximine (BSO), an inhibitor of GSH synthesis, has been shown to increase PC-3 prostate carcinoma cell cytotoxicity to melphalan. 39 Depletion of intracellular thiols and shifting the redox potential to a more reduced state has also been demonstrated in vitro, as a means of sensitizing Bcl-2 overexpressing human prostate tumor cell lines to radiation-induced apoptosis. 40 BSO, however, has been shown to be unable to enhance significantly the potentiation of cytotoxicity of melphalan and other chemotherapeutic agents, including menadione and helanlin, in other tumor cell lines.…”
Section: Figure 2 (Continued)mentioning
confidence: 97%
“…In addition, it has been shown that acquired resistance to cisplatin and alkylating agents is frequently accompanied by an elevation in intracellular GSH content [2+26]. Depletion of intracellular GSH as a strategy to increase the cytotoxic response to various chemotherapeutic agents in a variety of tumour cell lines has been the subject of a number of studies [27]. The majority of these have focused on bifunctional alkylating agents, although this approach has also proved useful in increasing the cytotoxicity of doxorubicin and platinum complexes both in cell culture and in in situ tumours [27].…”
Section: Reduced Glutathione (Gsh)/g Lutat (Gst)-mediated Resistance mentioning
confidence: 99%
“…Depletion of intracellular GSH as a strategy to increase the cytotoxic response to various chemotherapeutic agents in a variety of tumour cell lines has been the subject of a number of studies [27]. The majority of these have focused on bifunctional alkylating agents, although this approach has also proved useful in increasing the cytotoxicity of doxorubicin and platinum complexes both in cell culture and in in situ tumours [27]. GSTs are a family of multifunctional proteins that act both as enzymes and as binding proteins in various detoxification and excretory pathways.…”
Section: Reduced Glutathione (Gsh)/g Lutat (Gst)-mediated Resistance mentioning
confidence: 99%